Oxidative stress–mediated synergistic deleterious effects of nano- and microplastics in the hypoxia-conditioned marine rotifer Brachionus plicatilis. (August 2022) - Lee, Yoseop; Kim, Min-Sub; Park, Jordan Jun Chul; Lee, Young Hwan; Lee, Jae-Seong
Abstract: While pollution due to nano- and micro-sized plastics (NMPs) and hypoxic conditions both occur in coastal areas, the deleterious potential of co-exposure to hypoxia and NMPs (hypoxia and micro-sized plastics, HMPs; hypoxia and nano-sized plastics, HNPs) is largely unclear. Here, we provide evidence for multigenerational effects of HMP and HNP in the marine rotifer Brachionus plicatilis by investigating changes in its life traits, antioxidant system, and hypoxia-inducible factor (HIF) pathway using an orthogonal experimental design, with nanoscale and microscale particles measuring 0.05 μm and 6.0 μm in diameter, respectively, and hypoxic conditions of 0.5 mg/L for six generations. Combined exposure to NMPs and hypoxia caused a significant decrease in fecundity and overproduction of reactive oxygen species (ROS). The HIF pathway and circadian clock genes were also significantly upregulated in response to HMP and HNP exposure. In particular, synergistic deleterious effects of HNP were evident, suggesting that size-dependent toxicity can be a major driver of the effects of hypoxia and NMP co-exposure. After several generations of exposure, ROS levels returned to basal levels and transcriptomic resilience was observed, although rotifer reproduction remained suppressed. These findings help eluciating the underlying molecular mechanisms involved in responses to plastic pollution in hypoxic conditions. Highlights: Combined exposure to NMPs and hypoxia caused a significant decrease in fecundity and overproduction of ROS. The HIF pathway and circadian clock genes were significantly upregulated in response to HMP and HNP exposure. Synergistic and deleterious effects of HNP were evident. Size-dependent toxicity can be a major driver of the effects of hypoxia and NMP co-exposure. ROS levels returned to basal levels and transcriptomic resilience was observed after several generations of exposure.